In vitro digestibility and Caco-2 cell bioavailability of sea lettuce (Ulva fenestrata) proteins extracted using pH-shift processing. (15th September 2021) - Trigo, João P.; Engström, Niklas; Steinhagen, Sophie; Juul, Louise; Harrysson, Hanna; Toth, Gunilla B.; Pavia, Henrik; Scheers, Nathalie; Undeland, Ingrid
Highlights: We concentrated Ulva proteins 3.5-times using a scalable and food-grade process. pH-shift process improved the protein degree of hydrolysis of Ulva. Amino acid accessibility was higher in pH-shift protein extracts than in crude Ulva. The accessible amino acids of all samples were as bioavailable as those in casein. pH-shift process increased the amounts of amino acids transported across the cells. Abstract: Seaweed is a promising sustainable source of vegan protein as its farming does not require arable land, pesticides/insecticides, nor freshwater supply. However, to be explored as a novel protein source the content and nutritional quality of protein in seaweed need to be improved. We assessed the influence of pH-shift processing on protein degree of hydrolysis (%DH), protein/peptide size distribution, accessibility, and cell bioavailability of Ulva fenestrata proteins after in vitro gastrointestinal digestion. pH-shift processing of Ulva, which concentrated its proteins 3.5-times, significantly improved the %DH from 27.7±2.6% to 35.7±2.1% and the amino acid accessibility from 56.9±4.1% to 72.7±0.6%. Due to the higher amino acid accessibility, the amount of most amino acids transported across the cell monolayers was higher in the protein extracts. Regarding bioavailability, both Ulva and protein extracts were as bioavailable as casein. The protein/peptide molecular size distribution after digestion did not disclose a clear association with bioavailability.